Formação continuada para professores e aspirantes à docência no curso superior de administração: em foco a afetividade - Moura, Liliane Bonfim de (2014)
In this study, we aimed to analyze the process of continuing education for teachers and aspiring to teaching in Higher Administration course prioritizing affectivity It is considered that the career teacher in the upper reaches of Directors refers to specific characteristics of the area and that, as a rule, the teacher brings in her luggage only professional experience, without having in its constitution as a teacher a course aimed at teaching practices justifies analyze the process triggered by the said course. The theoretical foundation of this work was the theory of Henri Wallon and was based on studies of affectivity of Almeida (2002 , 2010,2011 ), Mahoney (2005.2011 ), Tardif (2008 ), among others. The methodology chosen was qualitative approach was used for the production of information : Description of modules 1 (Be Teacher in Higher Education ) and 2 (Curriculum and Pedagogical Knowledge ); description of the activities of the modules referred tutor (who was the researcher ); questionnaire administered to students of expertise provided by the Pro - Administration Project. The results also indicate that as the affectivity is one of the constitutive dimensions of the person, everything that happened in the course affected, but each, in its uniqueness, was affected differently, even though the technology as a major ally in the process teaching and learning, the face meetings are still of great importance in process of teaching and learning